Sistem Penunjang Keputusan Pemilihan Supplier Pakaian Jadi Menggunakan Metode Weighted Product (WP) Berbasis Web (Studi Kasus: Toko Mrz_Distro Tanah Abang) - Sri Rama Putri; Siti Marfirah (CV. Multi Kreasi Media, 2024)
Supplier is a company or individual that is able to provide resources, either in the form of goods or services needed by other companies. Supplier selection is the most important factor to improve sales quality. Mrz_Distro store is a store that sells various kinds of distro clothing. Mrz_Distro stores do not produce their own goods to be sold, but must find suppliers or other suppliers who have stock of goods according to demand. So far, supplier selection is still determined only by looking at price and quality subjectively. So that the Mrz_Distro shop is often wrong in choosing a clothing supplier as a provider of goods to be sold. Therefore, it is necessary to have a decision support system that can assist stores in determining suppliers that are in accordance with store requests. The method used is the weighted product (WP) method which was chosen because the concept is simple, easy to understand in solving practical decision making and this method speeds up the process of calculating criteria values and ranking for each alternative.